Natural Product-Based Discovery of Antibacterial Agents from Sophora tomentosa L. to Tackle Drug Resistance - Supattra Poeaim; Patcharanun Laowklang; Narumon Tangthirasunun; Thanarak Chantaraprasit (My University, 2025)
The rapid emergence of antimicrobial resistance (AMR) threatens global health by reducing the effectiveness of current antibiotics. Natural products remain an essential source of structurally diverse compounds with therapeutic potential. This study’s methanolic extracts of Sophora tomentosa L., a leguminous plant with traditional medicinal uses, were fractionated by liquid–liquid extraction and column chromatography. Dichloromethane and ethyl acetate fractions from leaves and seeds exhibited antibacterial activity against Kocuria rhizophila and Bacillus cereus. GC–MS profiling revealed alkaloids (e.g., matrine), flavonoids (e.g., catechin), phthalic acid derivatives, and fatty acids, supporting the potential of S. tomentosa as a source of novel antibacterial agents.
Keywords: Bioactive natural compounds; Bioactive Compounds in Plants; Natural Compound Pharmacology Studies